Concrete repair to EN 1504 : diagnosis, design, principles, and practice - Raupach, Michael (Boca Raton : Taylor & Francis, 2014)
'Preface Concrete Repair: Diagnosis, Design, Principles and Practice based on European Standards Michael Raupach and Till B
Includes bibliographical references and index.
Keywords: Concrete construction -- Maintenance and repair; Concrete -- Defects; TECHNOLOGY & ENGINEERING / Civil / General; TECHNOLOGY & ENGINEERING / Structural